TAXATION AND CORPORATE CULTURE IN THE COMPETENCE OF INTEGRATED LATIN AMERICAN MARKET - Hennings Otoya, Julio Alberto (2015)
The present work shows from a Peruvian perspecti-ve, the negative impact of tax and business culture variables of national agents compared to other MILA countries; considering among others: the taxation of capital gains applied in Peru and the limited propensity of local firms to use capital markets. The research is des-criptive and explanatory, using secondary sources in data collection, reports and data of the SMV and stock markets from MILA. Additionally, experts interviewed directors of the Superintendence of Securities and a representative Broker Company (SAB), with the aim of contrasting assessments of the findings.